Spanish Criminal Policy on Intimate partner violence: why "tough on crime" strategies are failing - Carrera, Enara Garro (International e-journal of criminal sciences, 2018)
The aim of this paper is to describe how the "tough on crime" policies on intimate partner violence have not been effective at all in Spain. Even if prevention of violence against women involves necessarily more than educational strategies and targeting cultural practices or social structures that support or consolidate this violence, deterrence through holding perpetrators accountable in the criminal justice system is not a panacea. Not only has using high repression levels through inflexible and very intrusive penalties not solved the problem, but it has also created new dysfunctions. The lack of consistent guiding principles in the elaboration of the criminal strategy of violence against women and the introduction of diverse legislative amendments on the spur of the moment has resulted in an amount of inefficient provisions, which even re-victimize and criminalize the women that don't behave in the way the criminal justice system expects.